A new inland record of the bull shark Carcharhinus leucas (Müller & Henle 1839) from Peninsular Malaysia - Hasan, Veryl; Samitra, Dian; Widodo, Maheno S.; Gausmann, Peter (Penerbit Universiti Kebangsaan Malaysia, 2021)
A single specimen of a bull shark Carcharhinus leucas (Müller & Henle 1839) with c. 102 cm of total length was landed and photographed on 25 March 2019 in Sungai Mawai Lama, about 25 km inland, Kota Tinggi District, Johor, Peninsular Malaysia. This rare finding represents only the second record of C. leucas in inland Peninsular Malaysia. This shark was identified as C. leucas by the snout much shorter than the width of mouth and bluntly rounded, first dorsal fin triangular, rearward sloping, originating over or slightly behind pectoral insertion, second dorsal fin much smaller than the first dorsal fin (< 3.1:1), and lack of an interdorsal ridge. The coloration of fresh specimen: greyish back and white belly, the dark coloration on the tip of the caudal fins and second dorsal fin. This species is currently listed as a vulnerable species based on the IUCN Red List Status. Further study and monitoring are needed to assess the possibility of the importance of Sungai Mawai Lama as critical habitat of C. leucas.